Intervensi Asuhan Komplementer dengan Metode Massage terhadap Peningkatan Produksi ASI : Literature Review - Senditya Indah Mayasari; Nicky Danur Jayanti (Oksitosin : Jurnal Ilmiah Kebidanan, 2023)
Complementary care in intervention of breastfeeding problems is currently being carried out a lot, one of which is the massage method. The massage method is considered effective and easy to do in tackling breastfeeding problems, especially to increase breast milk production. The objective of study was to find out complementary care interventions with massage methods to increase breast milk production. The research method used literature reviews related to breastfeeding and massage using electronic database. The databases used were Google Scholar, Pubmed, ResearchGate. Obtained 11 articles and carried out a review. The result study showed Oxytosin Massage method, Oketani Massgae, Woolwich Massage, Marmet Wolwich Massage, Combination Method of SPEOS, BOMB, Woolwich Massage and Rolling Massage effectively increase breast milk production. Massage method intervention in breastfeeding mothers can stimulate nerve cells in the breast which are then transmitted to the hypothalamus and responded through the anterior pituitary gland to produce the hormone prolactin, which will be transported by blood to epithelial cells in the breast, and increase the volume of breast milk. In addition, the effect of massage can relieve fatigue and stress, and mothers feel more comfortable and relaxed during breastfeeding.